Implementing Pre-trial Conference to Indonesia’s Criminal Justice System: Optimize the State Asset Recovery in Corruption Cases - Meika Arista; Hari Purwadi (Jurnal Hukum dan Pembangunan Ekonomi, 2025)
The corruption cases in Indonesia have been escalating over five years with a huge gap between state asset losses and state asset recovery. Moreover, it also getting worst with the lack of regulation in asset seizure and the low compensation verdicts for corruptors. These phenomena indicate a failure in the Indonesia’s criminal justice system. This study aims to introduce the concept of Pre-Trial Conference in Indonesia’s criminal justice system which can optimize the role of state victims and recover the state asset losses through the Plea Bargain concept. Several countries have implemented this concept in their criminal justice systems, including Singapore and Australia. The method used is a normative researchs with comparative legal analysis. The results of the study show that Pre-Trial Conference can be used as a formal and official judicial forum to provide corruptors with the opportunity to demonstrate their remorse by returning at least 60 percent of the total losses incurred. This concept aims to solve the legal issues by focusing on economic analysis and re-orientation on criminal sanction. The conclusion of this study is that Pre-Trial Conference is a solution to create a restorative justice and optimize the state asset recovery in corruption cases.